2017
DOI: 10.1111/jgs.14799
|View full text |Cite
|
Sign up to set email alerts
|

The Frailty Phenotype and Palliative Care Needs of Older Survivors of Critical Illness

Abstract: Background/Objectives To assess symptoms in older (age ≥65 years) intensive care unit (ICU) survivors and determine whether post-ICU frailty identifies those with the greatest palliative care needs. Design A prospective cohort study. Setting An urban tertiary-care hospital and community hospital. Participants One-hundred and twenty-five medical-ICU survivors of mechanical ventilation age ≥65 years. Measurements Baseline measurements of the Edmonton Symptom Assessment Scales (ESAS), categorized as mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 49 publications
1
41
0
1
Order By: Relevance
“…Because we focused on recipients who survived to discharge, we cannot directly compare the prevalence of frailty in our cohort with other studies in solid organ transplant. Among older adult survivors of a medical ICU admission, almost 80% were frail at discharge, higher than 54.1% of recipients who were frail in our cohort, likely reflecting population and disease differences . As with the broader transplant literature, however, we found that frailty was independent of other commonly used measures of functional impairment, including age and 6‐minute walk test .…”
Section: Discussionsupporting
confidence: 45%
“…Because we focused on recipients who survived to discharge, we cannot directly compare the prevalence of frailty in our cohort with other studies in solid organ transplant. Among older adult survivors of a medical ICU admission, almost 80% were frail at discharge, higher than 54.1% of recipients who were frail in our cohort, likely reflecting population and disease differences . As with the broader transplant literature, however, we found that frailty was independent of other commonly used measures of functional impairment, including age and 6‐minute walk test .…”
Section: Discussionsupporting
confidence: 45%
“…Evidence was mixed for the occurrence of other physical symptoms including shortness of breath (less problematic than for COPD or ALS, 28 but more problematic than non-frail, 42 poor quality evidence estimating 45% prevalence 40 ); drowsiness (higher than in non-frail, 42 but less so than ALS, COPD and ESRD 28 ); fatigue/weakness (less problematic than for COPD or ALS, 28 but more problematic than non-frail, 42 with poor quality evidence of 30% prevalence 40 ); loss of appetite (similarly problematic to non-frail, 42 with poor quality evidence of 38% prevalence 40 ) and pressure ulcers (similarly problematic to dementia, but lower than for cancer 27 ). There was poor quality evidence from a non-comparative study that two-fifths or more people with frailty have problems with weakness, sleeplessness, insomnia and loss of weight.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies examined the psychosocial needs of people with frailty nearing the end of life, one of good quality, 28 two fair 27,42 and four poor quality. 26,36,40,41 There was evidence that people with frailty experience similar study defined ‘emotional distress’ (emotional distress with psychological symptoms that are sustained, intense, progressive and not related to acute concurrent conditions) to people with cancer from one fair quality study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific criteria diagnosing frailty during ICU stay are not available. Poor appetite and nutritional intake [19,309] may be evident. Frailty is more frequent in the elderly population (50% in patients older than 80 years) and is associated with increased mortality.…”
Section: Commentary To Recommendations 41 -43mentioning
confidence: 99%